IMPROVING PERFORMANCE THROUGH APPLICATIONS ON GRABFOOD DRIVERS PT. GRAB INDONESIA IN SURABAYA CITY - Massaid, Muhammad Alif; Winarsih, Tutik (Transpublika Publisher, 2024)
Currently, it is known that the use of the internet and electronic goods in Indonesia has increased drastically with the emergence of online buying and selling sites and services. The increase in online buying and selling systems and online food delivery services has led to the emergence of new applications such as Go-Jek, Grab, In-Driver and others, where these applications provide many kinds of services such as 2-wheeled and 4-wheeled delivery services, food delivery services, delivery services. goods, shopping services, house cleaning services and many more. This research aims to determine the performance of Grabfood PT drivers. Grabfood Indonesia since there were changes to the Grabfood application in the city of Surabaya. The approach used in this research is descriptive. The population in this study were all Grabfood PT drivers. Grab Indonesia in Surabaya City. The sample used in this research used quota sampling of 60 drivers in the city of Surabaya. The data collection techniques used in this research were interviews and questionnaires. The results of this research show the performance of Grabfood PT drivers. Grab Indonesia is positive regarding changes to the Grabfood application.